The Effect of Lactation Counseling on Mothers' Breastfeeding Ability with the LATCH Method Approach - Purnamasari, Kurniati Devi; Suminar, Ratna; Laksmidara, Adinda; Maharanie, Stephanie Putri; Patimah, Auliya Nur Hajah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Breastfeeding success is influenced by a mother's breastfeeding skills. The LATCH score is an instrument used to objectively assess breastfeeding skills. However, many postpartum mothers still experience difficulties breastfeeding due to a lack of understanding of correct breastfeeding techniques. Counseling on breastfeeding techniques is an effort that can improve postpartum mothers' ability to breastfeed optimally. Objective: To determine the effectiveness of breastfeeding technique counseling on postpartum mothers' breastfeeding skills based on the LATCH score. Methods: This study used a quasi-experimental design with a pretest-posttest control group approach. The sample consisted of postpartum mothers who met the inclusion criteria (n =50), divided into an intervention group and a control group. The intervention group received breastfeeding technique counseling for 4 sessions, while the control group received standard care. The breastfeeding skills instrument used the LATCH observation sheet. Data analysis was performed using paired t-tests and independent t-tests. Results: The average LATCH score in the intervention group increased significantly after counseling (p < 0.05), while the control group showed no significant change. There was a significant difference in LATCH scores between the intervention and control groups after treatment. Conclusion: Breastfeeding technique counseling effectively improved postpartum mothers' breastfeeding skills, as measured by LATCH scores.